Why the current Peak in Populism in the US and Europe? Populism as a Deviation in the Median Voter Theorem - Filipa Figueira (European Journal of Government and Economics (EJGE), 2018)
The current surge of populism in Europe and the United States calls for further analysis using public choice tools. In this article, populism is modelled as a deviation from the normal state of the median voter theorem. This study adds to the public choice literature by proposing a model of populism which is suited, not only to left-wing populism, but also to other forms of populism prevalent in Europe and the United States today. It is argued that, due to changes in the assumptions underpinning the median voter theorem, the operation of the model can be modified, and as a result surges of populism occur. Those assumptions concern: the political spectrum; the distribution of ideological preferences; sociological, psychological and historical factors; political party competition; and extreme political preferences. It is shown that the current peak of populism in Europe and the United States can be explained through a simultaneous change in all of these aspects, leading to a “perfect storm” of populism.
Keywords: 330; Populism; Median Voter Theorem; Public Choice; Ideologies; Rational Choice